THE INFLUENCE OF STORYTELLING TOWARDS THE STUDENTS’ SPEAKING SKILL (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2022)
Some of the difficulties in learning English in the Speaking aspect in class X SMA Negeri 1 Subang. Researchers assume that students are not used to speaking in English which is caused by many factors. Therefore, by looking at these conditions, researchers conducted research using a method that could hone students' speaking skills, namely the Storytelling method. The purpose of this study was to determine whether there was an effect of storytelling on students' speaking skills, using the Quasi-Experimental method, using 2 classes, namely the Control class and the Experiment class. The method developed in this study has a positive impact on students, one of which is that students become more confident when they start speaking in English, while also making students more responsive and enthusiastic in learning. Hopefully this research can be a means of developing students' talents and abilities, especially in speaking English
Keywords: Speaking; Storytelling; Method; Skill